2022
DOI: 10.1007/s43546-022-00392-2
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the relationship between organizational performance, dynamic capabilities and strategic behavior

Abstract: Current business challenges mean that understanding elements that can affect organizational performance represents a differential factor in maintaining competitiveness. In this context, the objective of this article is to conduct a Systematic Literature Review (SLR) of the relationship between dynamic capabilities, strategic behavior, and organizational performance. For this, A three-stage SLR protocol was used: (i) planning, (ii) conduct, and (iii) knowledge development. A total of 118 articles covering the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…(2018) reported the moderating role of controlling and enabling uses of management control system for the effect of environmental innovation strategy on firm performance. Our finding on the moderation mechanism of knowledge acquisition also addressed the call for investigations into moderators related to organizational learning in Drago et al. ’s (2022) review of the effect of strategic changes on organizational performance.…”
Section: Discussionsupporting
confidence: 58%
“…(2018) reported the moderating role of controlling and enabling uses of management control system for the effect of environmental innovation strategy on firm performance. Our finding on the moderation mechanism of knowledge acquisition also addressed the call for investigations into moderators related to organizational learning in Drago et al. ’s (2022) review of the effect of strategic changes on organizational performance.…”
Section: Discussionsupporting
confidence: 58%
“…The concepts of strategic capabilities and the sustainable competitive advantage have provoked many academic discussions for several years (Teece, 2019). Understanding capabilities that can impact organizational performance and sustainability is pivotal for retaining the sustainable competitive advantage (SCA) given the current business complexities (Drago, et al, 2023). The effort by firms to undertake strategic actions that allow for the SCA against rivals in same industry is facing a major challenge in the modern, evolving business environment (Islami, Mustafa, & Topuzovska Latkovikj, 2020).…”
Section: Background Of the Studymentioning
confidence: 99%
“…In Brazil, Drago et al (2023) investigated how institutional performance was affected by dynamic capabilities strategic planners. Systematic Literature Review [SLR] was adopted which covered planning conduct and development of knowledge.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The results revealed that the dynamic capabilities of strategic planners influenced positively and increased the competitive intensity of the organization with other institutions. However, Drago et al (2023) relied on secondary data which is often prone to biases on authors' opinions rather than the reality.…”
Section: Empirical Reviewmentioning
confidence: 99%